PENGEMBANGAN MODUL IPA MELALUI PENDEKATAN SAINTIFIK PADA TEMA ROTASI DAN REVOLUSI BUMI SEBAGAI IMPLEMENTASI KURIKULUM 2013 - Muhammad Ali; Faisal Batennie (STKIP Paris Barantai, 2016)
The purpose of research and development, namely: (1) develop a science module through a scientific approach to the theme of the rotation and revolution of the earth, (2) the results of student learning after the learning process using science module through a scientific approach to the theme of the rotation and revolution of the earth. Methods used in research and development Research and Development (R & D). Development implemented by referring to the model ADDIE (Analyse, Design, Development, Implementation, Evaluation) proposed by Russell and Molenda. Science module validation is assessed on the feasibility of the content, presentation, and language by lecturers, teachers, and peer review. Based on the validation of the feasibility of the content, presentation and language science modules to be eligible to use and implemented in class VIII.B SMPN 1 Pulau Sembilan Kotabaru District. Student learning outcomes were analyzed with nonparametric tests using the Wilcoxon test is processed using IBM SPSS Statistics 20 software. Results of research and development: (1) science module through a scientific approach to the theme of the rotation and revolution of the Earth was developed using a scientific approach components using ADDIE models include Analyse, Design, Development, Implementation, and Evaluation, (2) the results of student learning after the learning process using science module through a scientific approach to the theme of the rotation and revolution of the earth has increased significance. Improving student learning outcomes seen from the p-value of -4.462 below (<0.05). Keyword: science module, scientific approach, ADDIE.